Contenido de amilosa, proteínas y grado de blancura en arroces comercializados comparados con dos líneas avanzadas - Candelario Lara, Dalerman Alexander (2024)
The present research work “Amylose content, protein and degree of whiteness in marketed rice and compared with two advanced lines”. It has a high level of importance since it informs the consumer or producer of the quality of the grain. The objective of this research is to determine the content of amylose, protein and whiteness in different brands of rice in the local market compared with two advanced lines of rice. A parametric design is used for statistical analysis. 22 varieties of rice will be used with three repetitions. In this process, the FACIAG grain laboratory is used to dry, clean, husk, polish, obtain powder, rice, measure the content of amylose, proteins and the degree of whiteness. The variables that were evaluated were: Percentage (%) of amylose content, percentage (%) of proteins and the degree (%) of whiteness. Regarding the results, all the variables were statistically significant. This study determined that commercial rice brands have slightly similar milling characteristics and meet the standards that currently exist in Ecuador.